Sistem Pendukung Keputusan Berbasis Metode Topsis untuk Rekomendasi Pengadaan Alat Kesehatan: (Studi Kasus Dinas Kesehatan) (Mars: Jurnal Teknik Mesin, Industri, Elektro Dan Ilmu Komputer, 2025)
The development of information technology has brought significant changes to the medical device procurement process, particularly within government institutions such as the Health Office. The procurement of appropriate, efficient, and objective medical devices is crucial to supporting optimal medical services, yet the decision-making process is often constrained by limited budgets and the complexity of multiple assessment criteria. This study aims to design and implement a decision support system (DSS) based on the TOPSIS (Technique for Order Preference by Similarity to Ideal Solution) method to provide recommendations for medical device procurement at the Binjai Health Office. The DSS evaluates six main criteria: price, quality, durability, ease of maintenance, medical necessity, and safety level, using procurement data from the 2022–2024 period. The TOPSIS method is applied to calculate the relative closeness of each alternative to the ideal solution, enabling decision-makers to rank medical device options objectively and systematically. The findings show that the DSS successfully prioritizes procurement alternatives, helping stakeholders allocate budgets more effectively and transparently. In addition, the system minimizes subjective bias by integrating quantitative analysis with clearly defined criteria. The system is implemented in a web-based environment with MySQL as the database, ensuring accessibility and scalability for future use. Overall, this research demonstrates that integrating TOPSIS into a decision support system can enhance the efficiency, accuracy, and accountability of medical device procurement in public health agencies. The study is expected to contribute to improving budget management and strengthening the quality of health services through better resource allocation.